Respuesta :
Answer:
a
The Doolittle version of factorization A =UL is
[tex]\left[\begin{array}{ccc}a_{11}&a_{12\\a_{21}&a_{22}\end{array}\right] =\left[\begin{array}{ccc}a_{11}-a_{12}*\frac{a_{21}}{a_{22}} &a_{12}\\0&a_{22}\end{array}\right]\left[\begin{array}{ccc}1&0\\\frac{a_{21}}{a_{22}} &1\end{array}\right][/tex]
b
Algorithm
1) Obtain the values of the individual elements of U and L
[tex]U_{22} = a_{22}[/tex]
[tex]l_{21} = \frac{a_[21} {U_{22}}}[/tex]
[tex]U_{12} = a_{12}[/tex]
[tex]U_{11} = a_{11} - U_{12}*l_{21}[/tex]
2) Obtain the value of z for the expression [tex]Uz = b[/tex] 1.e
[tex]\left[\begin{array}{ccc}U_{11}&U_{12\\0&U_{22}\end{array}\right] \left[\begin{array}{ccc}z_1\\z_2\end{array}\right] =\left[\begin{array}{ccc}b_1\\b_2\end{array}\right][/tex]
[tex]z_2 =\frac{b_2}{U_22}[/tex]
[tex]z_1 = \frac{1}{U_[11}} [b_1 - U_{12}\ z_2][/tex]
3 Obtain the value of x for the expression [tex]Lx = z[/tex] 1.e
[tex]\left[\begin{array}{ccc}1&0\\l_{21}&1\end{array}\right] \left[\begin{array}{ccc}x_1\\x_2\end{array}\right] = \left[\begin{array}{ccc}z_1\\z_2\end{array}\right][/tex]
[tex]x_1 = z_1[/tex]
[tex]x_2 = z_2 -l_{21}x_1[/tex]
c
Let say that [tex]A^T =LU[/tex] is the Doolittle factorization of [tex]A^T[/tex]
where L is a unit lower triangular matrix and U is upper triangular matrix
Hence [tex]A = U^T L^T[/tex]
Here [tex]L^T[/tex] is a unit upper triangular matrix and [tex]U^T[/tex] lower is triangular
In the question that we are given A = UL meaning that [tex]A^T = L^TU^T[/tex] looking at this U is upper triangular matrix and L is unit lower triangular matrix. So we can say that the Doolittle version given behave like Doolittle factorization only for A and there is no connection with [tex]A^T[/tex]
Step-by-step explanation:
From the question let assume that [tex]A =\left[\begin{array}{ccc}a_{11}&a_{12\\a_{21}&a_{22}\end{array}\right][/tex]
The objective is to find the Doolittle version of the factorized A = UL and this can be expressed in matrix as
[tex]\left[\begin{array}{ccc}a_{11}&a_{12\\a_{21}&a_{22}\end{array}\right] =\left[\begin{array}{ccc}U_{11}&U_{12\\0&U_{22}\end{array}\right]\left[\begin{array}{ccc}1&0\\l_{21}&1\end{array}\right][/tex]
Looking at this in form of matrix multiplication
[tex]a_{11} =U_{11} +U_{12} l_{21}[/tex]
[tex]a_{12} = U_{12}[/tex]
[tex]a_{21} = U_{22} l_{21}[/tex]
[tex]a_{22} = U_{22}[/tex]
=> [tex]l_{21} = \frac{a_{21}}{U_{22}} = \frac{a_{21}}{a_{22}}[/tex]
and [tex]u_{11} = a_{11} - U_{12}l_{21} = a_{11} -a_{12} *\frac{a_{21}}{a_{22}}[/tex]
Hence [tex]U = \left[\begin{array}{ccc}a_{11}-a_{12}*\frac{a_{21}}{a_{22}} &a_{12}\\0&a_{22}\end{array}\right][/tex]
[tex]L = \left[\begin{array}{ccc}1&0\\\frac{a_{21}}{a_{22}} &1\end{array}\right][/tex]
b) From the question we are given
[tex]Ax =b[/tex]
And objective is to describe the algorithm to solve it
[tex]Ax =b[/tex]
[tex]UL x = b[/tex]
Let assume that [tex]z = Lx[/tex]
So
[tex]U z = b[/tex]
Given that U is upper triangular matrix then y can be obtained by back substitution
Now that we are able to obtain y, given that L is a unit lower triangular matrix we can obtain x by forward substitution
The algorithm is given in the answer section